1994
DOI: 10.1007/bf00007949
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility management as a factor in weed control: the effect of crimson clover residue, synthetic nitrogen fertilizer, and their interaction on emergence and early growth of lambsquarters and sweet corn

Abstract: Previous experiments have shown that crimson clover (Trifolium incarnatum L.) used as a green manure may supply weed control benefits as well as nitrogen (N) to a subsequent crop of corn (Zea mays L.). In contrast to use of synthetic N fertilizer, use of fresh, incorporated crimson clover residue as an N source has been found to suppress lambsquarters (Chenopodium album L.) aboveground drymatter accumulation but to only temporarily reduce that of sweet corn. One possible cause of the clover's suppressive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 17 publications
3
44
0
1
Order By: Relevance
“…2). Our results agree with previous reports of potent red clover residue affects on wild mustard (Ohno and Doolan 2001) and common lambsquarters emergence (Dyck and Liebman 1994). We found some seed germination in fresh residue treatments starting on day 16 (Fig.…”
Section: Microbial Interactions With Solid Residue Fractionssupporting
confidence: 93%
“…2). Our results agree with previous reports of potent red clover residue affects on wild mustard (Ohno and Doolan 2001) and common lambsquarters emergence (Dyck and Liebman 1994). We found some seed germination in fresh residue treatments starting on day 16 (Fig.…”
Section: Microbial Interactions With Solid Residue Fractionssupporting
confidence: 93%
“…At Ridgetown, N treatment had no effect on sweet corn shoot biomass production at any time during the sweet corn season, likely due to high plant available N over the growing season (data not shown). Other research has also shown that fertilization does not necessarily lead to increased sweet corn biomass or plant populations (Dyck and Liebman 1994;Mullins et al 1999;Teasdale et al 2008). Similarly, others have found that neither cover crops (Teasdale et al 2008;Burgos and Talbert 1996) nor N treatment (Isse et al 1999) had an effect on sweet corn biomass.…”
Section: Yield and Profit Marginsmentioning
confidence: 94%
“…The soil surface is noticeably wetter and warmer under hairy vetch monocultures, and its prostrate growth habit results in rapid decomposition even while the plant is still growing [53]. Since N is known to stimulate both weed germination and growth [54], grass/legume mixtures that delay N release allow producers to address both weed and N management needs. However, as we discuss in greater detail below, grass/legume mixtures decrease the overall N available for a corn crop when compared to a pure legume cover crop and, thus, may require supplemental sources of N.…”
Section: Cover Crops and Weed Control In Cornmentioning
confidence: 99%